2021
DOI: 10.2478/dine-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dapagliflozin-induced expression profile of long noncoding RNAs in proximal tubular epithelial cells of diabetic kidney disease

Abstract: Background Accumulating evidence indicates that long noncoding RNAs (lncRNAs) play an important role in diabetic kidney disease (DKD). Dapagliflozin (DAPA), a sodium-glucose cotransporter 2 (SGLT2) inhibitor, exerts protective effects against DKD, but the underlying mechanism remains unclear. Methods In this study, we performed RNA microarray analysis to investigate differentially expressed lncRNAs and mRNAs in human proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Zhang (35) demonstrated that miRNA-29a inhibited HG-induced podocytes pyroptosis and alleviated inflammatory response by directly targeting NLRP3. Song et al (36) revealed that miR−520c−3p reduced HK-2 cell pyroptosis induced by HG through inhibiting TXNIP/NLRP3 inflammasome pathway.…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Zhang (35) demonstrated that miRNA-29a inhibited HG-induced podocytes pyroptosis and alleviated inflammatory response by directly targeting NLRP3. Song et al (36) revealed that miR−520c−3p reduced HK-2 cell pyroptosis induced by HG through inhibiting TXNIP/NLRP3 inflammasome pathway.…”
Section: Non-coding Rnasmentioning
confidence: 99%